Extremely low prevalence of intestinal cryptosporidiosis and hygienic practices among hospitalized children with malignancies in Malaysia: a preliminary observation - Elbeshti, Lubna Mohamed; Nimir, Amal Rashad; Osman, Malina; Unyah, Ngah Zasmy; Ithnin, Nur Raihana; Abdul Rahman, Eni Juraida; Abdullah, Wan Omar; Hamat, Rukman Awang (Academic Journals, 2011)
Intestinal cryptosporidiosis has been reported to be associated with high morbidity and mortality among cancer patients. The objectives of the study were to determine the prevalence of cryptosporidiosis and to elucidate contributing factors that might influence its transmission in our children with cancer. A prospective cross-sectional study among 110 patients hospitalized for chemotherapy and 100 healthy children (used as controls) between November 2009 and January 2011 at Institute of Paediatrics, Malaysia. Stools were screened for Cryptosporidium by using RIDA-quick Cryptosporidium (RBiopharm, Germany) and underwent formalin-ether concentration method and stained with modified Ziehl-Neelsen stain as a gold standard. Questionnaires on personal hygiene practices and risk factors, and medical records from 105 children were analyzed. All stool samples were negative for Cryptosporidium. Washing hands before and after taking meals and after using the toilet were practised in 85/105 (80.9%) and 79/105 (75.2%), respectively. History of previous hospitalization was observed in 35/105 (33.3%), contact with animals 31/105 (29.5%), swimming in the pools 26/105 (24.8%) and admission to day care centres in 17/105 (16.2%). History of drinking unfiltered tap water and recent travel were seen in 3/105 (2.9%) and 1/105 (0.9%), respectively. Intestinal cryptosporidiosis is very rare among children with cancer and good personal hygiene practices remain the best preventive approach.